God said this - Winkler, Leah Nanako (Yale drama series., 2019)
The 2018 winner of the Yale Drama Series competition is a riveting exploration of family and death Set in Kentucky, this compelling drama centers around a Japanese-American family reunited as their matriarch undergoes cancer treatment. The father, James, is a recovering alcoholic seeking redemption, and the two daughters are struggling to overcome their differences--Sophie is an ardent born-again Christian, while Hiro lives a single's life in New York City. John, an old high school classmate of Hiro's who is now a single dad, worries about leaving a legacy for his son. Wry and bittersweet, God Said This vividly captures the complexities of a familial reconciliation in the throes of crisis and looks deeply at the meaning of family--Japanese, Southern, and otherwise. This is the first Yale Drama Series winner chosen by Pulitzer prize-winning playwright Ayad Akhtar, who describes the play as conveying "a deeply felt sense of the universal--of the perfection of our parents' flawed love for each other and for us; for the ways in which the approach of death can order the meaning of a human life."